Fauna edáfica em diferentes sistemas de manejo: avaliações sob a ótica acadêmica e do conhecimento local - Schiavon, Greice de Almeida (2012)
This study was conducted on Estação Experimental Cascata, Embrapa Clima Temperado, in Pelotas, and on one family farm, in Morro Redondo. The objective of the study was to evaluate the scientific and local knowledge about the influences of management practices on soil fauna in ecological production systems. The methodology for samples of soil fauna, in each season, was done using the TSBF (Tropical Soil Biology and Fertility). Local knowledge was assessed using semi-structured interviews. The data analysis was done using th ecological indices as explanatory tools, and also the multivariate analysis (Principal Component Analysis - PCA) to evaluate the influence of management practices on soil fauna. In the first chapter, the ecological horticultural production systems cultivated under laminar composting with manure (CE) and mulch on the soil (CM), at Embrapa, showed the best values of soil fauna diversity, while treatment with frequent soil mechanization (MF) obtained a strong correlation with enchytraeids in all seasons. In the second chapter, results from interviews showed that the studied family recognize the role of earthworms in soil and understand the influence of the soil practices on soil fauna. It s possible to conclude that local knowledge is a valuable contribution to scientific knowledge to assess the influence of management practices on soil fauna. Moreover, the treatments CE and CM demonstrated their importance for to maintaining the soil diversity and for decreasing the hand labor in ecological horticultural production systems.